1999
DOI: 10.1111/j.1600-0714.1999.tb02108.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tobacco smoking and of betel chewing with tobacco on the buccal mucosa: a cytomorphometric analysis

Abstract: The effect of tobacco use on the buccal mucosa has been assessed by cytomor‐phometry. Cell and nuclear diameters (CD, ND) of exfoliated oral squames were measured in tobacco smokers (S), betel chewers with tobacco (C) and those with a combined habit (S + C). Non‐users (NU) served as controls. The mean CD values in S, C, S + C and NU were: 50.8 (± 0.47), 49.39 (± 0.48), 49.12 (±0.47) and 51.87 (± 0.76) urn, and the mean ND values were: 8.83 (± 0.07), 8.61 (± 0.08), 8.72 (± 0.10) and 8.33 (± 0.09) um, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 25 publications
(21 reference statements)
2
49
2
Order By: Relevance
“…However, in the buccal cells of individuals with malignant lesions 11,13 or of smokers, 12,15 alterations distinct from those in the present study were found. In individuals with a tobacco-chewing habit and in those with smoking and tobacco-chewing habits combined, an increase in nuclear diameter and a decrease in cell diameter were observed, 15 as were seen in samples of individuals with tumors in the mouth floor.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…However, in the buccal cells of individuals with malignant lesions 11,13 or of smokers, 12,15 alterations distinct from those in the present study were found. In individuals with a tobacco-chewing habit and in those with smoking and tobacco-chewing habits combined, an increase in nuclear diameter and a decrease in cell diameter were observed, 15 as were seen in samples of individuals with tumors in the mouth floor.…”
Section: Discussioncontrasting
confidence: 81%
“…In individuals with a tobacco-chewing habit and in those with smoking and tobacco-chewing habits combined, an increase in nuclear diameter and a decrease in cell diameter were observed, 15 as were seen in samples of individuals with tumors in the mouth floor. 13 Cowpe et al 11 did not find size changes in the nucleus in samples of suspicious lesions of the buccal mucosa and the mouth floor but did observe a decrease in cytoplasmic area in lesions of the buccal mucosa.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies have reported the effect of different types of diseases and aggressive agents on oral mucosa, such as alcohol, and tobacco 10,12,[20][21][22][23][24][25] . However, studies reporting physical trauma associated to use of orthodontic appliances are still scarce 8 .…”
Section: Resultsmentioning
confidence: 99%
“…These include radiotherapy, smoking, alcohol, and malignant oral lesions. Therefore, the effects of such factors, if present, should be taken into account when assessing a lesion under investigation (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%